Efektifitas Pengelolaan Dana Zakat melalui Program Z-MART di BAZNAS Kota Tangerang (Studi Kasus Pada BAZNAS Kota Tangerang) - Abdul Rachman; Kukuh Kukuh (STES Islamic Village, 2021)
This study aims to analyze how effective the management of zakat funds is through the Z-Mart program carried out by the Tangerang City National Amil Zakat Agency to be able to help small stalls belonging to mustahik zakat in capital, business management and branding. This study uses qualitative methods to describe the management of zakat funds through the Z-Mart program. The source of this research data was taken through observations at several small stalls belonging to mustahik zakat which were selected and fostered in the Z-Mart program. The researcher also conducted interviews with several core and supporting informants, such as the person in charge of the Z-Mart program at the Tangerang City National Amil Zakat Agency, zakat mustahik who own a small shop, consumers and others. Other data are taken from various documentations, articles and others related to research. The results of this study illustrate that the management of zakat funds carried out by the Tangerang City National Amil Zakat Agency has been effective in Z-Mart branding. However, in terms of business management and the capital needed by small stalls, the Z-Mart program is deemed less effective because the capital provided is still lacking because there are many mustahik needs as poor asnaf who have to meet the needs of their family's life, especially when in a situation like this their income. down from before the pandemic.